Exploring the Anticancer Potential of MonoHER (7-Mono-O-(β-Hydroxyethyl)-Rutoside): Mitochondrial-Dependent Apoptosis in HepG2 Cells - Chujie Li; Yue Wang; Jian Liang; Guido R. M. M. Haenen; Yonger Chen; Zhengwen Li; Ming Zhang; Ludwig J. Dubois (Current Issues in Molecular Biology)
Background/Aim: Flavonoids are a group of polyphenols, abundantly present in our diet. Although, based on their chemoprotective effects, intake of flavonoids is associated with a high anticancer potential as evidenced in in vitro and in vivo models, the molecular mechanism is still elusive. This study explores the antiproliferative and cytotoxic effects of the semi-synthetic flavonoid MonoHER (7-mono-O-(β-hydroxyethyl)-rutoside) in vitro on cancer cells. Materials and Methods: HepG2 liver, MCF7 breast, and H1299 lung cancer cells were grown under ambient conditions with or without MonoHER exposure. CCK8 assay was used to assess cell viability. Apoptosis, JC-1, and mitochondrial mass were determined using flow cytometry and confocal analysis. The effects of monoHER on apoptosis proteins were detected by confocal microscopy analysis and Western blot. Results: It was found that MonoHER can reduce HepG2 cells’ and MCF7 cells’ viability, but not H1299 cells’, and induced apoptosis only in HepG2 cells. MonoHER has the potential to enhance the expression of caspase-9 and caspase-3, to damage mitochondria, and to provoke the release of cytochrome C from the mitochondria. Conclusion: MonoHER can inhibit cell growth and induce apoptosis especially in HepG2 human liver cancer cells by triggering the mitochondrial signal transduction pathway, leading to the release of cytochrome C in the cytoplasm and the subsequent activation of caspase-9 and caspase-3. Future research should further explore MonoHER’s mechanism of action, efficacy, and potential for clinical translation.